Psychological health in people having suffered from COVID-19: predictors - Angelucci Bastidas, Luisa; Rondón Bernard, José Eduardo (Población y Salud en Mesoamérica, 2025)
Introduction: It is estimated that a significant percentage of people who have suffered from COVID-19 may continue to experience physical symptoms and psychological health sequels. There are different psychosocial factors that could potentially explain and predict the health of COVID-19 survivors. In this sense, the aim of this study was to explore how gender, age, educational level, loss of close relatives due to the disease, oxygen assistance, post-COVID-19 chronic disease diagnosis, and the physical and psychological difficulties suffered, affect the psychological health of people having suffered from COVID-19. Method: A prospective single-group study was implemented, and a participation of 419 individuals was registered, of both sexes, selected via a purposive sampling. Two instruments were administered: The Goldberg General Health Questionnaire, to measure social dysfunction, anxiety and depression; and a second instrument designed for this research, to evaluate sociodemographic, and disease-related variables. Results: The model explaining the greatest percentage of variance is one of social dysfunction (16 %), compared to another one of anxiety and depression (14 %). On the other hand, being female (B = -.15; B = -.22), younger (B = -.28; B = -.16), and having physical (B = .17; B = .14) or psychological (B = .2; B = .13) difficulties, seems to predict higher levels of social dysfunction and of anxiety and depression. Post-COVID-19 chronic illness diagnosis (B = .11) predicts only the levels of anxiety and depression. Conclusion: Considering the results, it is recommended to design psychosocial programs aimed at addressing the psychological health of individuals having suffered from COVID-19. Results of the study shall be analyzed considering sampling limitations.